2021
DOI: 10.1021/acssuschemeng.0c08026
|View full text |Cite
|
Sign up to set email alerts
|

Respirometry and Cell Viability Studies for Sustainable Polyesters and Their Hydrolysis Products

Abstract: Significant research effort has been directed toward the development of sustainable plastics that are high-performance, bioderived, and/or degrade into nontoxic byproducts in natural or engineered environments (i.e., industrial composting facilities). We report the low cytotoxicity of poly(γ-methyl-ε-caprolactone) (PMCL)-based materials and the hydrolysis product of PMCL, sodium 6-hydroxy-4-methylcaproate. The concentration of sodium 6-hydroxy-4-methylcaproate that leads to 50% cell death (TD 50 ) is 179 mM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Furthermore, a modified Gompertz growth model was used to fit the experimental data for the respirometry method (eq S4), which was used to determine the biodegradation rate coefficient ( R m ) of P3­(HA) samples. The model has been used previously for industrial composting, anaerobic biodegradation, and other microbial growth modeling. The parameters of the modified Gompertz model are reported in Table . By inspecting the rate constant R m values, it can be seen that there is good agreement among the biodegradation rates of P3­(HA) samples.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a modified Gompertz growth model was used to fit the experimental data for the respirometry method (eq S4), which was used to determine the biodegradation rate coefficient ( R m ) of P3­(HA) samples. The model has been used previously for industrial composting, anaerobic biodegradation, and other microbial growth modeling. The parameters of the modified Gompertz model are reported in Table . By inspecting the rate constant R m values, it can be seen that there is good agreement among the biodegradation rates of P3­(HA) samples.…”
Section: Resultsmentioning
confidence: 99%
“…PSMG was rapidly degradable under industrial composting conditions in later research. [32] The short time for PSMG to reach the maximum conversion of polymer to CO 2 was <30 days, which is much better than PET and even many compostable and sustainable polymers.…”
Section: Regioselective Rop Of Aromatic Diestersmentioning
confidence: 98%
“…Accordingly, PLA has become one of the most widely used biodegradable polymers for packaging, multifilament fibers for textile applications, and as substrates for transient electronics. However, there are two major issues with using PLA in transient electronics: (i) the aggressive conditions required for complete degradation, 34 and (ii) the brittleness of the polymer, prompting the need for alternatives.…”
Section: Bioderived Source Materialsmentioning
confidence: 99%
“…3(B)). Recent reports have also found that PGSM can reach 89% carbon mineralization after 120 days under industrial composting conditions, 34 making it an attractive candidate for a wide range of disposal methods.…”
Section: Degradation Of Transient Electronicsmentioning
confidence: 99%
See 1 more Smart Citation